Development Of A Low Electric Field Dna Electrophoresis Microchip Featuring Amperometric Detection - Ghanim, Motasem H H (2013)
Everyday inventions of microelectronics and micro-devices are advancing towards converting the Microchip Capillary Electrophoresis (MCE) devices into a true Micro Total Analysis System (μTAS) or Lab-On-a-Chip (LOC) microsystem that can perform the whole analytical procedures in-situ. Electrochemical detection (ECD) is one of the best means for designing a LOC or μTAS systems especially for separation and detection of electroactive analytes, as in biomedical and in vitro diagnostics. The most widely targeted electroactive analytes is nucleic acid. DNA genotyping or fingerprinting has been recognized as one of the most important applications of these micro devices. DNA fingerprinting is normally used in electrophoretic applications of analytical chemistry such as DNA sequencing and detection, identification of pathogenic microorganism like microbe fungus, and disease diagnostics. However, there are some major obstacles in realizing miniaturized and mass-producible MCE systems, such as high manufacturing cost, and the bulky power supply unit which make the whole system none-portable. In this project, a low cost as well as low electric field MCE utilizing an amperometric detection scheme was designed and fabricated for DNA sequencing and detection. The device was fabricated from a glass/polydimethylsiloxane (PDMS) hybrid engraved microchannel with platinum electrodes sputtered onto a glass substrate. It has been established that, the use of Agarose gel as separation material could reduce the electric field to as low as 12 V/cm; this has not been achieved previously.